Biographical research as a methodology for understanding entrepreneurial marketing. Issue 3 (5th May 2015) - David Higgins, Professor Kiran Trehan and Professor Pauric McGowan, Dr; Fillis, Ian
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to respond to the Special Issue call by developing the case for enhancing understanding of entrepreneurial marketing by utilising biographical research. This builds on the limited existing research in entrepreneurial marketing using this approach. Design/methodology/approach – Five entrepreneurial marketers are assessed using biographical research. Findings – The individuals assessed clearly show the connection between the telling of a life story and how a business is run using an entrepreneurial marketing approach. Biographical techniques succeed in addressing the need for situation specific understanding. Entrepreneurial marketing core competencies help establish competitive advantage through their ability to influence behaviour, market creation and growth activities. Research limitations/implications – Biographical research contributes towards the additional theoretical and practical insight which entrepreneurial marketing requires. Practical implications – Entrepreneurial marketers can make use of biographical research findings due to their readability and association with their own practices to help shape future strategies. Originality/value – The biographical approach has been underutilised in entrepreneurial marketing research. These research results enhance existing understanding of the foundations of entrepreneurial marketing.